Eco Cycle Mobile: A Design Thinking Approach for Sustainable User Interface and User Experience Design - Rini Indriati; Ning Inge Halimah Silva; Delilla Anandita; Sucipto (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2026)
The Eco Cycle system is a mobile-based circular economy platform designed to increase public participation in sustainable waste management activities. The development of a mobile-based Eco Cycle application is urgent because it addresses usability and accessibility issues and supports sustainable behavior change through interactive, educational, and collaborative digital experiences. The objective of the research is to develop a User Interface and User Experience prototype for a circular- conomybased Eco Cycle mobile application to increase public participation in sustainable waste management, environmental engagement, and circular-economy activities. The research method employs a Design Thinking approach comprising Empathy, Definition, Ideation, Prototype, and Testing. The application prototype integrates several key features: ECOSell and ECOBuy for waste buying and selling services, ECOducation for environmental education, ECOmmunity for community collaboration, ECOPlanner for waste management planning, and ECOPoint as a participation-based system. The results of the study indicate that a usability evaluation using the User Experience Questionnaire and an open-ended questionnaire yielded positive user experiences across all UEQ dimensions. The highest scores for the attractiveness (1.87) and stimulation (1.80) dimensions were categorized as very good. The efficiencydimension scored 1.85, dependability 1.53, and novelty 1.26, categorized as good. Carity scored 1.71, categorized as above average. Additional usability analysis demonstrated high task completion rates and positive user perceptions of the ease of transactions, system resources, and environmental interaction features. The study concludes that the Design Thinking approach is effective for developing a user-centric mobile application that supports environmentally friendly behavior and increases community participation in circular-economy-based waste management.